All-solid-waste mine filling cementing material as well as preparation method and application thereof
By using all-solid waste mine filling cementitious materials and taking advantage of the synergistic effect of solid waste components such as red mud and steel slag and additives, the problems of high cost and insufficient strength of cement-based grouting materials are solved, and a high-strength, low-cost underground filling effect is achieved.
Patent Information
- Application Number
- CN202510879412.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional cement-based grouting materials are expensive and difficult to use on a large scale in underground filling operations. At the same time, their alternative materials are difficult to ensure good strength performance while reducing costs.
The all-solid waste mine filling cementitious material is used. By using solid waste components such as red mud, steel slag, manganese slag, and slag as alkali sources and highly active silicon-aluminum materials, and adding fillers and additives such as aluminum sulfate and nano-nucleating agents, the formation of CSH gel and ettringite is promoted to form a high-strength cementitious material.
Good results of underground filling operations were achieved while reducing costs. The strength of cementitious materials far exceeds that of traditional cement-based materials and can serve as an ideal substitute for them.
Smart Images

Figure BDA0005472021760000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of mine filling materials, and more specifically, to a full-solid waste mine filling gelling material and a preparation method and application thereof. Background Art
[0002] Thermal disasters are the primary cause of coal mine accidents. As the severity of accidents increases, the proportion of these accidents in major and serious coal mine accidents also increases. During coal mining, accidents such as gas outbursts, fires, and water inrushes frequently occur. Mine fires, in particular, have a significant impact on safe coal mining. Statistics show that among China's more than 600 key and centrally managed coal mines, over half mine coal seams prone to spontaneous combustion, and spontaneous combustion fires account for over 90% of all fires.
[0003] Spontaneous combustion of coal in goaf areas is a common disaster in coal mines. It not only wastes significant amounts of coal energy but also easily triggers secondary hazards such as gas and coal dust explosions, seriously threatening mine safety and production. Grouting fire prevention and extinguishing technology has been developed in the context of coal mine fire management. Its main principle is to fill the voids in coal mine tunnels with grouting material, creating a confined space that prevents the spread of fire and secondary fires after a disaster. Traditional grouting materials include mud and cement-based materials.
[0004] Regarding the aforementioned related technologies, the inventors believe that while cement-based grouting materials can provide a certain sealing effect, their relatively high application cost makes them difficult to apply on a large scale in underground filling operations. While using cement alternatives may reduce costs, they struggle to guarantee adequate strength. Summary of the Invention
[0005] In related technologies, cement-based grouting materials are expensive, making them difficult to apply on a large scale in underground filling operations. Alternative products to cement-based grouting materials also struggle to maintain sufficient strength while saving costs. To address this shortcoming, this application provides a fully solid waste mine filling cementitious material, its preparation method, and its application.
[0006] In the first aspect, the present application provides a fully solid waste mine filling cementitious material, which adopts the following technical solution: a fully solid waste mine filling cementitious material, comprising the following components in parts by weight: 100 parts of solid waste components, 0.3-1.2 parts of additives, wherein the solid waste components include the following components in weight percentage: 15-25% of alkali source, 12-17% of industrial gypsum waste residue, 1.6-1.8% of filler, and the balance is supplemented to 100% by high-activity silicon-aluminum materials; the alkali source includes red mud and steel slag, the filler includes iron tailings powder, the high-activity silicon-aluminum material includes manganese slag and slag, and the components of the additive include aluminum sulfate and nano-nucleating agent.
[0007] By adopting the above technical solution, the present application uses solid waste components and additives to prepare mine filling cementitious materials. Among the solid waste components, red mud and steel slag are used as alkali sources, manganese slag and slag are used as highly active silicon-aluminum materials, and filler components are also added. The main component in the slag is glass, which can undergo hydration reaction under the synergistic stimulation of the alkali source and industrial gypsum waste slag to produce CSH gel and calcium aluminate, which is the main source of system strength. In addition to the active silicon-aluminum components, manganese slag also contains a certain amount of gypsum components, which can synergistically promote the hydration of glass in the slag with the alkali source and industrial gypsum waste slag. The surface of the iron tailings powder has a certain electronegativity, which can attract the attachment and precipitation of calcium ions, and can synergistically induce the directional growth of CSH gel with the nano-nucleating agent in the additive, thereby promoting the formation of CSH gel, and the aluminum sulfate in the additive can promote the formation of the calcium aluminate skeleton, further promoting the development of strength. Under the synergistic effect of alkali source, industrial gypsum waste residue, filler and high-activity silicon-aluminum material, the all-solid waste mine filling cementitious material of this application can have higher strength and can be used as an ideal substitute for cement-based grouting material. Moreover, since the solid waste components can be directly taken from stockpiled solid waste, the production cost is extremely low, and good underground filling effect can be achieved under the condition of reducing costs.
[0008] Preferably, the alkali source also includes carbide slag.
[0009] By adopting the above technical solution, carbide slag is an alkaline waste produced by the carbide industry, and its main component is calcium hydroxide. It can supplement the calcium component of the cementitious material system of this application and increase the alkalinity of the system, thereby improving the synergistic effect of the alkali source and industrial gypsum waste slag, promoting the hydration reaction of highly active silica-alumina materials, and making the formation of CSH gel and calcium aluminate more thorough, which helps to improve the overall strength of the cementitious material for all-solid waste mine filling.
[0010] Preferably, the alkali source also includes steelmaking dust.
[0011] By adopting the above technical solution, steelmaking dust is one of the difficult-to-treat solid wastes generated by steel enterprises. It contains a large amount of iron oxide mineral phase, which can promote the formation of hydrated tricalcium ferroaluminate in the system, accelerate the hardening of the material, and can synergize with the calcium aluminate skeleton to promote the development of overall strength, thereby improving the strength of the all-solid waste mine filling cementitious material.
[0012] Preferably, the auxiliary agent further comprises calcium nitrate.
[0013] By adopting the above technical solution, the present application also selects calcium nitrate as a component of the auxiliary agent. Calcium nitrate has a certain early strength effect and can synergistically promote the formation of CSH gel with alkali source, industrial gypsum waste residue and nano nucleating agent, which helps to improve the strength of the all-solid waste mine filling cementitious material.
[0014] Preferably, the auxiliary agent further comprises ferric nitrate.
[0015] By adopting the above technical solution, ferric nitrate can react with calcium hydroxide to produce ferric hydroxide gel and calcium nitrate. The ferric hydroxide gel can synergistically fill the pores inside the cementitious system with the CSH gel and synergistically promote the development of strength with the ettringite skeleton. Calcium nitrate can synergistically promote the formation of CSH gel with the alkali source, industrial gypsum waste residue and nano-nucleating agent, thereby helping to fully improve the strength of the cementitious material for all-solid waste mine filling.
[0016] Preferably, the nano nucleating agent comprises modified nano alumina, and the modified nano alumina is prepared according to the following method: (1) Anhydrous ethanol and nano-alumina are mixed, and after ultrasonic dispersion, a nanoparticle dispersion liquid is obtained, which is set aside; water and anhydrous ethanol are mixed, glacial acetic acid is added to adjust the pH, and a silane coupling agent is added to obtain a silane solution, which is set aside; (2) The nanoparticle dispersion and the silane solution are mixed, and after constant temperature stirring and heating, centrifugal separation and centrifugal washing are performed, and the obtained solid is dried and ground to obtain modified nano-alumina.
[0017] By adopting the above-mentioned technical solution, the present application modified the nano-alumina with a silane coupling agent, adding silane segments to the surface of the nano-alumina, improving its dispersion and reducing its agglomeration. The nano-alumina synergistically interacted with iron tailings powder, an alkali source, and industrial gypsum waste, fully promoting the growth of CSH gel, thereby effectively improving the strength properties of the all-solid waste mine fill cementitious material.
[0018] Preferably, the nano-nucleating agent further comprises CFSH nano-crystal cores, and the CFSH nano-crystal cores are prepared according to the following method: (1) Prepare sodium silicate solution, calcium nitrate-ferric nitrate mixed solution and PCE solution with deionized water and set aside; (2) The PCE solution is stirred, and a sodium silicate solution and a calcium nitrate-ferric nitrate mixed solution are added to the PCE solution while stirring, and the pH of the mixed solution is adjusted with a sodium hydroxide solution and a nitric acid solution. After the addition is completed, the stirring reaction is continued to obtain a suspension, and the suspension is dried to obtain CFSH nanocrystal cores.
[0019] By adopting the above-mentioned technical solution, the present application adds ferric nitrate to the process of preparing CSH nanocrystalline cores, resulting in CFSH nanocrystalline cores. The addition of iron salts results in smaller particle sizes for the CFSH nanocrystalline cores. Furthermore, the iron-containing component synergistically improves the dispersion of the CFSH nanocrystalline cores with PCE. Furthermore, the iron-containing component synergizes well with iron tailings powder, alkali sources, and industrial gypsum waste, effectively promoting the growth of CSH gel and improving the strength properties of all-solid waste mine fill cementitious materials.
[0020] Preferably, the filler further comprises shell powder, and the average particle size of the shell powder is 3-5 μm.
[0021] By adopting the above technical solution, the present application preferably uses shell powder as a component of the filler. Shell powder belongs to the calcite phase and can adsorb calcium ions in the gelling system. It has a strong adsorption capacity and can synergize with nano-nucleating agents and iron tailings powder to promote the production of CSH gel. In addition, the good filling effect of shell powder can fully improve the strength of the full-solid waste mine filling cementitious material.
[0022] In a second aspect, the present application provides a method for preparing a fully solid waste mine filling cementitious material, which adopts the following technical solution.
[0023] A method for preparing a fully solid waste mine filling cementitious material comprises the following steps: (1) mixing an alkali source, industrial gypsum waste residue, a filler, and a high-activity silicon-aluminum material to obtain a solid waste component; (2) The solid waste components are mixed with additives to obtain a fully solid waste mine filling cementitious material.
[0024] By adopting the above technical solution, the present application first prepares the solid waste components, and then adds the additives to the solid waste components to obtain a full-solid waste mine filling cementitious material that is sufficient to replace cement.
[0025] In a third aspect, the present application provides an application of a fully solid waste mine filling cementitious material, which adopts the following technical solution.
[0026] The invention discloses an application of a full-solid waste mine filling cementitious material, comprising mixing the full-solid waste mine filling cementitious material with fine aggregate and water to prepare a slurry, and then using the slurry to perform underground filling operations.
[0027] By adopting the above-mentioned technical solution, the present application mixes the all-solid waste mine filling cementitious material with fine aggregate and water to prepare a slurry, which is then used for underground filling operations. The fine aggregate in this process can also be produced using solid waste, which can effectively reduce the cost of underground filling operations and facilitate large-scale operations.
[0028] In summary, this application has the following beneficial effects: 1. This application uses solid waste components and additives to formulate a mine filling cementitious material. Among the solid waste components, red mud and steel slag are used together as an alkali source, manganese slag and slag are used together as a highly active silicon-aluminum material, and a filler component is also added. Under the synergistic effect of the alkali source, industrial gypsum waste residue, filler, and highly active silicon-aluminum material, the all-solid waste mine filling cementitious material of this application can have high strength and can serve as an ideal substitute for cement-based grouting materials. In addition, because the solid waste components can be directly taken from stockpiled solid waste, the production cost is extremely low, and good underground filling effects can be achieved while reducing costs.
[0029] 2. This application uses a silane coupling agent to modify nano-alumina, adding silane segments to the surface of nano-alumina, improving the dispersion performance of nano-alumina, and reducing the agglomeration of nano-alumina. Therefore, nano-alumina can fully promote the growth of CSH gel and improve the strength performance of the all-solid waste mine filling cementitious material.
[0030] 3. This application incorporates ferric nitrate into the preparation process of CSH nanocrystal cores to produce CFSH nanocrystal cores. The addition of iron salts results in smaller particle sizes for the CFSH nanocrystal cores. Furthermore, the iron component, in combination with PCE, synergistically improves the dispersion of the CFSH nanocrystal cores, fully promoting the growth of CSH gels and improving the strength of the all-solid waste mine fill cementitious material. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the Examples, Preparation Examples and Comparative Examples. The raw materials involved in the present application can all be obtained commercially.
[0032] Preparation example of modified nano-alumina The following is an explanation using Preparation Example 1.
[0033] Preparation Example 1 In this preparation example, modified nano-alumina was prepared according to the following method: (1) Anhydrous ethanol and nano-alumina with an average particle size of 70 nm were mixed in a weight ratio of 25:1, and after ultrasonic dispersion, a nanoparticle dispersion was obtained, which was set aside; water and anhydrous ethanol were mixed in a weight ratio of 1:1, glacial acetic acid was added to adjust the pH to 3.5, and then a silane coupling agent KH550 was added to obtain a silane solution, which was set aside; in this step, the amount of silane coupling agent KH550 used was 3% of the total weight of the nano-alumina; (2) The nanoparticle dispersion and the silane solution were mixed in a weight ratio of 9:1, heated at 70°C with constant stirring (stirring speed 420 r / min) for 4 h, and then centrifuged and washed. The obtained solid was dried and ground to obtain modified nano-alumina.
[0034] Preparation Example of CSH Nanocrystal Core The following is an illustration of Preparation Example 2.
[0035] Preparation Example 2 In this preparation example, CSH nanocrystal cores were prepared according to the following method: (1) Prepare sodium silicate solution, calcium nitrate solution and PCE solution with deionized water and set aside; in this preparation example, calcium nitrate and sodium silicate are used in a molar ratio of 1.2:1, PCE is a polycarboxylate water-reducing agent with a water-reducing rate of 32%, and the amount of PCE is 1% of the total weight of calcium nitrate and sodium silicate; (2) The PCE solution was stirred, and sodium silicate solution and calcium nitrate solution were added to the PCE solution while stirring, and the pH of the mixed solution was adjusted to 11.7 using sodium hydroxide solution and nitric acid solution. After the addition was completed, the stirring reaction was continued for 24 hours to obtain a suspension, and the suspension was dried to obtain CSH nanocrystal cores.
[0036] Preparation Examples of CFSH Nanocrystal Cores The following is an illustration of Preparation Example 3.
[0037] Preparation Example 3 In this preparation example, CFSH nanocrystal cores were prepared according to the following method: (1) Prepare a sodium silicate solution, a calcium nitrate-ferric nitrate mixed solution, and a PCE solution with deionized water and set aside; in this preparation example, calcium nitrate, ferric nitrate, and sodium silicate are used in a molar ratio of 1:0.2:1, PCE is a polycarboxylate water-reducing agent with a water-reducing rate of 32%, and the amount of PCE is 1% of the total weight of calcium nitrate, ferric nitrate, and sodium silicate; (2) The PCE solution was stirred, and sodium silicate solution and calcium nitrate-ferric nitrate mixed solution were added to the PCE solution while stirring, and the pH of the mixed solution was adjusted to 11.7 using sodium hydroxide solution and nitric acid solution. After the addition was completed, the stirring reaction was continued for 24 hours to obtain a suspension, and the suspension was dried to obtain CFSH nanocrystal cores. Example
[0038] Examples 1-3 The following description will be given using Example 1 as an example.
[0039] Example 1 In this embodiment, the alkali source includes red mud and steel slag, the weight ratio of red mud to steel slag is 2:1, the red mud is Bayer red mud with an average particle size of 70 μm, and the steel slag is converter steel slag with an average particle size of 85 μm; the filler is iron tailings powder with an average particle size of 120 μm; the industrial gypsum waste slag is a mixture of desulfurized gypsum, phosphogypsum and fluorgypsum in a weight ratio of 4:1:1; the high-activity silicon-aluminum material includes manganese slag with an average particle size of 65 μm and slag with an average particle size of 50 μm, and the weight ratio of manganese slag to slag is 1:3; the components of the auxiliary agent include aluminum sulfate and nano-nucleating agent, the weight ratio of aluminum sulfate to nano-nucleating agent is 2:1, and the nano-nucleating agent is nano-alumina with an average particle size of 70 nm.
[0040] This embodiment provides a fully solid waste mine filling cementitious material, comprising the following components in parts by weight: 100 kg of solid waste components, 0.3 kg of additives, and the solid waste components comprising the following components in weight percentage: 15% of alkali source, 17% of industrial gypsum waste residue, 1.6% of filler, and the remainder being supplemented to 100% by high-activity silicon-aluminum materials.
[0041] This embodiment provides a method for preparing a cementitious material for filling a solid waste mine, comprising the following steps: (1) mixing an alkali source, industrial gypsum waste residue, a filler, and a high-activity silicon-aluminum material to obtain a solid waste component; (2) The solid waste components are mixed with additives to obtain a fully solid waste mine filling cementitious material.
[0042] This embodiment also provides an application of a fully solid waste mine filling cementitious material, comprising mixing the fully solid waste mine filling cementitious material with fine aggregate and water to prepare a slurry with a solid content of 70% and a lime-sand ratio of 1:10, and then using the slurry for underground filling operations, wherein fine aggregate is selected.
[0043] As shown in Table 1, the differences between Examples 1-3 mainly lie in the different raw material ratios of the all-solid waste mine filling cementitious materials.
[0044] Table 1 Raw material ratio of all-solid waste mine filling cementitious materials Example 4 The difference between this embodiment and embodiment 3 is that the alkali source further includes carbide slag, and the weight ratio of carbide slag to steel slag is 1:1.
[0045] Example 5 The difference between this embodiment and embodiment 4 is that the alkali source further includes steelmaking dust (iron oxide mineral phase content 48.3 wt%), and the weight ratio of steelmaking dust to steel slag is 0.2:1.
[0046] Example 6 The difference between this embodiment and embodiment 5 is that the auxiliary agent further includes calcium nitrate, and the amount of calcium nitrate used is 0.3 kg.
[0047] Example 7 The difference between this embodiment and embodiment 6 is that the auxiliary agent further includes ferric nitrate, and the amount of ferric nitrate used is 0.2 kg.
[0048] Example 8 The difference between this embodiment and embodiment 7 is that the nano-nucleating agent is the modified nano-alumina prepared in preparation example 1.
[0049] Example 9 The difference between this embodiment and embodiment 8 is that the nano nucleating agent further includes CSH crystal nuclei, which are prepared according to the method of preparation example 2, and the weight ratio of CSH crystal nuclei to modified nano alumina is 1:1.
[0050] Example 10 The difference between this example and Example 9 is that the CSH crystal nuclei are replaced with CFSH crystal nuclei of the same weight, and the CFSH crystal nuclei are prepared according to the method of Preparation Example 3.
[0051] Example 11 The difference between this embodiment and embodiment 10 is that the filler further includes shell powder, the average particle size of the shell powder is 20 μm, and the weight ratio of the shell powder to the iron tailings powder is 1:1.
[0052] Example 12 The difference between this embodiment and Example 11 is that the average particle size of the shell powder is 5 μm.
[0053] Example 13 The difference between this embodiment and Example 11 is that the average particle size of the shell powder is 4 μm.
[0054] Example 14 The difference between this embodiment and Example 11 is that the average particle size of the shell powder is 3 μm.
[0055] Comparative Example Comparative Example 1 This comparative example uses P.O32.5 silicate cement as a reference.
[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that the components of the all-solid waste mine filling cementitious material do not include aluminum sulfate.
[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that the components of the all-solid waste mine filling cementitious material do not include a nano nucleating agent.
[0058] Comparative Example 4 The difference between this comparative example and Example 1 is that the solid waste component does not include an alkali source.
[0059] Comparative Example 5 The difference between this comparative example and Example 1 is that the solid waste component does not include industrial gypsum waste residue.
[0060] Comparative Example 6 The difference between this comparative example and Example 1 is that the solid waste component does not include a filler.
[0061] Performance testing methods According to the "JGJ T70-2009 Standard for Test Methods for Basic Properties of Building Mortar," iron ore tailings machine-made sand with a fineness modulus of 2.7 was used as fine aggregate. This sand was mixed with the all-solid waste mine fill cementitious material of each embodiment and comparative example (PO32.5 Portland cement in Comparative Example 1) to form a slurry with a solid content of 70% and a lime-sand ratio of 1:10. This slurry was then used to prepare cubic mortar specimens, and the 28-day compressive strength of the mortar specimens was tested. The results are shown in Table 2.
[0062] Table 2 Compressive strength sample Compressive strength / MPa sample Compressive strength / MPa Example 1 3.94 Example 11 4.21 Example 2 3.95 Example 12 4.23 Example 3 3.96 Example 13 4.24 Example 4 3.98 Example 14 4.24 Example 5 4.00 Comparative Example 1 2.77 Example 6 4.06 Comparative Example 2 3.50 Example 7 4.07 Comparative Example 3 3.40 Example 8 4.13 Comparative Example 4 3.28 Example 9 4.15 Comparative Example 5 3.33 Example 10 4.20 Comparative Example 6 3.49 Combining Examples 1-3 with Comparative Example 1 and Table 2, it can be seen that the compressive strength measured in Examples 1-3 is relatively high. This is because the present application causes a hydration reaction of the highly active silica-alumina material under the synergistic stimulation of the alkali source and industrial gypsum waste, and utilizes the gypsum component in the manganese slag for synergistic stimulation. Calcium ions are adsorbed by the iron tailings powder, and the nano-nucleating agent is used to induce the directional growth of the CSH gel. Aluminum sulfate can promote the formation of the ettringite skeleton. It can be seen that under the synergistic action of the alkali source, industrial gypsum waste, filler, and highly active silica-alumina material, the all-solid waste mine filling cementitious material of the present application can have a relatively high strength. The 28d compressive strength of the prepared specimens far exceeds that of the specimens prepared with 32.5 cement, making it an ideal substitute for cement-based grouting materials.
[0063] Combining Example 1 and Comparative Example 2 and Table 2, it can be seen that the compressive strength measured in Example 1 is higher. This is because Comparative Example 2 lacks aluminum sulfate, and aluminum sulfate cannot fully promote the formation of the ettringite skeleton, which ultimately affects the strength development of the specimen.
[0064] Combining Example 1 and Comparative Example 3 with Table 2, it can be seen that the compressive strength measured in Example 1 is higher. This is because Comparative Example 3 lacks a nano-nucleating agent, making it difficult to fully induce the directional growth of the CSH gel through the synergistic effect of the nano-nucleating agent and the iron tailings powder, which ultimately affects the strength development of the specimen.
[0065] Combining Example 1 and Comparative Examples 4-5 and Table 2, it can be seen that the compressive strength measured in Example 1 is higher. This is because Comparative Examples 4-5 cannot stimulate the activity of the high-activity silicon-aluminum material through the synergistic effect of the alkali source and industrial gypsum waste, which ultimately affects the strength development of the specimen.
[0066] Combining Example 1 and Comparative Example 6 with Table 2, it can be seen that the compressive strength measured in Example 1 is higher. This is because Comparative Example 6 lacks filler, making it difficult to fully induce the directional growth of CSH gel through the synergistic effect of the nano-nucleating agent and the iron tailings powder, which ultimately affects the strength development of the specimen.
[0067] Combining Example 3 and Example 4 and Table 2, it can be seen that the compressive strength measured in Example 4 is higher. This is because the alkali source in Example 4 contains carbide slag, which can supplement the calcium component of the cementitious material system of the present application and increase the alkalinity of the system, thereby improving the synergistic effect of the alkali source and industrial gypsum waste slag, promoting the hydration reaction of the highly active silica-alumina material, and making the formation of CSH gel and ettringite more thorough, which helps to improve the overall strength of the cementitious material for all-solid waste mine filling.
[0068] Combining Example 4 and Example 5 with Table 2, it can be seen that the compressive strength measured in Example 5 is higher. This is because the alkali source in Example 5 also includes steelmaking dust ash, which contains a large amount of iron oxide mineral phase, which can promote the formation of hydrated tricalcium ferroaluminate in the system, accelerate the hardening of the material, and can synergistically promote the development of overall strength with the ettringite skeleton, thereby improving the strength of the all-solid waste mine filling cementitious material.
[0069] Combining Examples 5 and 6 with Table 2, it can be seen that the compressive strength measured in Example 6 is higher. This is because calcium nitrate has a certain early strength effect and can synergistically promote the formation of CSH gel with the alkali source, industrial gypsum waste residue and nano-nucleating agent, which helps to improve the strength of the all-solid waste mine filling cementitious material.
[0070] Combining Example 6 and Example 7 with Table 2, it can be seen that the compressive strength measured in Example 7 is higher. This is because ferric nitrate can react with calcium hydroxide to produce ferric hydroxide gel and calcium nitrate. The ferric hydroxide gel can synergistically fill the pores inside the gelling system with the CSH gel and synergistically promote the development of strength with the ettringite skeleton. Calcium nitrate can synergistically promote the formation of CSH gel with the alkali source, industrial gypsum waste residue and nano-nucleating agent, thereby helping to fully improve the strength of the all-solid waste mine filling cementitious material.
[0071] Combining Example 7 and Example 8 with Table 2, it can be seen that the compressive strength measured in Example 8 is higher. This is because the silane coupling agent improves the dispersion performance of the nano-alumina and reduces the agglomeration of the nano-alumina. Therefore, the nano-alumina has a good synergistic effect with the iron tailings powder, the alkali source, and the industrial gypsum waste residue, which can fully promote the growth of the CSH gel, thereby effectively improving the strength performance of the all-solid waste mine filling cementitious material.
[0072] Combining Examples 8, 9-10, and Table 2, it can be seen that the compressive strength measured in Example 9 increases compared with that in Example 8, while the increase in Example 10 is even greater. This is because the addition of iron salts results in smaller particle sizes of the CFSH nanocrystalline cores, and the iron-containing component and PCE synergistically improve the dispersion of the CFSH nanocrystalline cores and produce a good synergistic effect with the iron tailings powder, alkali source, and industrial gypsum waste residue. Therefore, it can fully promote the growth of CSH gel and improve the strength performance of the all-solid waste mine filling cementitious material.
[0073] In combination with Example 10, Examples 11-14 and Table 2, it can be seen that the compressive strength measured in Examples 11-14 is relatively high, and the compressive strength measured in Examples 12-14 is significantly higher than that in Example 11. This is because shell powder belongs to the calcite phase and can adsorb calcium ions in the gelling system, and has a strong adsorption capacity. Within the particle size range specified in this application, it can synergistically promote the production of CSH gel with the nano-nucleating agent. Coupled with the good filling effect of shell powder, the strength of the full-solid waste mine filling cementitious material can be fully improved.
[0074] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application as needed without any creative contribution. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A full solid waste mine filling cementitious material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of solid waste components and 0.3-1.2 parts of auxiliary agents, wherein the solid waste components comprise the following components in weight percentage: 15-25% of an alkali source, 12-17% of industrial gypsum waste residue, 1.6-1.8% of a filler, and the balance is supplemented to 100% by a high-activity silicon-aluminum material; the alkali source comprises red mud and steel slag, the filler comprises iron tailings powder, the high-activity silicon-aluminum material comprises manganese slag and slag, and the components of the auxiliary agents comprise aluminum sulfate and a nano-nucleating agent.
2. The all-solid waste mine filling cementitious material according to claim 1, characterized in that: The alkali source also includes carbide slag.
3. The all-solid waste mine filling cementitious material according to claim 2, characterized in that: The alkali source also includes steelmaking dust.
4. The all-solid waste mine filling cementitious material according to claim 1, characterized in that: The components of the auxiliary agent also include calcium nitrate.
5. The all-solid waste mine filling cementitious material according to claim 4, characterized in that: The auxiliary agent also includes ferric nitrate.
6. The all-solid waste mine filling cementitious material according to claim 1, characterized in that: The nano nucleating agent includes modified nano alumina, and the modified nano alumina is prepared according to the following method: (1) Anhydrous ethanol and nano-alumina are mixed, and after ultrasonic dispersion, a nanoparticle dispersion is obtained, which is set aside; water and anhydrous ethanol are mixed, glacial acetic acid is added to adjust the pH, and a silane coupling agent is added to obtain a silane solution, which is set aside; (2) The nanoparticle dispersion and the silane solution are mixed, and after constant temperature stirring and heating, centrifugal separation and centrifugal washing are performed. The obtained solid is dried and ground to obtain modified nano-alumina.
7. The all-solid waste mine filling cementitious material according to claim 6, characterized in that: The nano nucleating agent further comprises CFSH nanocrystal cores, and the CFSH nanocrystal cores are prepared according to the following method: (1) Prepare sodium silicate solution, calcium nitrate-ferric nitrate mixed solution and PCE solution with deionized water and set aside; (2) The PCE solution is stirred, and sodium silicate solution and calcium nitrate-ferric nitrate mixed solution are added to the PCE solution while stirring, and the pH of the mixed solution is adjusted with sodium hydroxide solution and nitric acid solution. After the addition is completed, the stirring reaction is continued to obtain a suspension, and the suspension is dried to obtain CFSH nanocrystal cores.
8. The all-solid waste mine filling cementitious material according to claim 7, characterized in that: The filler further comprises shell powder, and the average particle size of the shell powder is 3-5 μm.
9. The method for preparing a cementitious material for filling solid waste mines according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mixing an alkali source, industrial gypsum waste residue, a filler, and a highly active silicon-aluminum material to obtain a solid waste component; (2) The solid waste components are mixed with additives to obtain a fully solid waste mine filling cementitious material.
10. The application of the all-solid waste mine filling cementitious material according to claims 1-8, characterized in that: The method includes mixing all-solid waste mine filling cementitious materials with fine aggregate and water to prepare slurry, and then using the slurry for underground filling operations.
Citation Information
Cited By
Carbide slag-based low-carbon gel material and preparation method thereof
CN121107767A
A dry powder premix for preparing a full-solid waste non-fired cementitious material from alkaline red mud and steel slag and a process thereof
CN122520381A
